2010
DOI: 10.1007/s11431-010-4043-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 60Co-gamma radiation on the random walk error of interferometric fiber optic gyroscopes

Abstract: Two 60 Co-gamma radiation experiments were launched to explore the radiation effect on optical components and interferometric fiber optic gyroscope (IFOG). In optical components radiation experiment, the result showed that polarization-maintaining (PM) fiber coil loss was the most affected parameter in all the RWC (random walk coefficient) related parameters, compared with the weak sensitivity of other components parameters. In the IFOG radiation experiment, the RWC performance degradation was found to be almo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Moreover, RWC is an important parameter of optical fiber gyro static index, which determines the minimum of the gyro testing phase shift. The RWC of the closed-loop operational IFOG with π/2 modulation phase can be expressed as [5] RWC = λ c 2πLD…”
Section: Effect Of Color Centers' Absorption On the Ifogsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, RWC is an important parameter of optical fiber gyro static index, which determines the minimum of the gyro testing phase shift. The RWC of the closed-loop operational IFOG with π/2 modulation phase can be expressed as [5] RWC = λ c 2πLD…”
Section: Effect Of Color Centers' Absorption On the Ifogsmentioning
confidence: 99%
“…[3,4] Furthermore, it affects the performance of the IFOGs in space environment. [5] The smaller optical power received by the photodetector resulting from the RIA can cause the degradation of random walk coefficient (RWC). In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Scott et al have measured the cross talk in ECore fibers and observed that the h parameter remained constant throughout the irradiation [8] . RIA in PM optical fiber, which can lead to a decrease of the optical power incident on the detector in IFOG [9] , and further result in the decrease of sensitivity [10] , is a significant factor that must be addressed. However, little information on the RIA in PM fibers for IFOG is available in literature, particularly for the state-of-the-art PM fibers made in China.…”
mentioning
confidence: 99%